Machine learning‐resistant pseudo‐random number generator. Issue 9 (1st May 2019) - Wen, Yiming; Yu, Weize
Abstract : Conventional pseudo‐random number generator (PRNG) is vulnerable to machine learning (ML) attacks since algorithms are used to generate the random number. Physical unclonable function (PUF) is a kind of hardware security primitive that can also be cracked by ML attacks. However, the main security difference between a regular PRNG and a PUF is that training the output data of a regular PRNG is sufficient to break the PRNG while the challenge‐to‐response pairs of a PUF must be available for a successful training. In order to design a ML‐resistant PRNG, in this Letter, the output data of a regular PRNG is fed into a PUF to generate the encrypted data first. Then the encrypted data is added to the output data of the other regular PRNG to create the output data for the ML‐resistant PRNG. Since the input challenge of the PUF is concealed, the adversary is unable to model the PUF with ML techniques. The result shows that the training accuracy of a single output bit of the ML‐resistant PRNG is only about 52.6% even if 200, 000 data are sampled for training. In contrast, only 50, 000 data are adequate to break a regular PRNG if ML attacks are executed.